Cost-effectiveness analysis of rezvilutamide versus bicalutamide and androgen-deprivation therapy in patients with high-volume, metastatic, hormone-sensitive prostate cancer: a Markov’s model-based evaluation - Hong, Juan; Zeng, Xiaohui; Chen, Wenjun; Zhou, Ziyuan; He, Yuming; Meng, Jun; Ouyang, Lihui (Frontiers in Public Health, 2025)
ObjectivesRezvilutamide, an androgen-receptor inhibitor, has been approved by the Chinese National Medical Products Administration as a first-line treatment for high-volume metastatic hormone-sensitive prostate cancer (mHSPC). This study aims to assess the cost-effectiveness of rezvilutamide plus androgen-deprivation therapy (ADT) compared to bicalutamide plus ADT for the first-line treatment of high-volume mHSPC in China.MethodsA Markov model with three health states was developed to evaluate the health and economic outcomes of first-line treatment for high-volume mHSPC. Efficacy data were sourced from the CHART trial. Quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs) were calculated. To address modeling uncertainties, one-way sensitivity analysis and probabilistic sensitivity analysis were performed.ResultsCompared with bicalutamide plus ADT, rezvilutamide plus ADT resulted in an additional 2.16 QALYs, with an ICER of 39,122.16/QALY. At a willingness-to-pay (WTP) threshold of three times the gross domestic product per capita in China for 2023 (37,256.3/QALY), the probability of cost-effectiveness for rezvilutamide plus ADT was 30%. One-way sensitivity analysis revealed that the results were most sensitive to the cost of rezvilutamide. Scenario analysis indicated that rezvilutamide could be considered cost-effective if priced below 705.46 per cycle.ConclusionFrom the perspective of Chinese payers, rezvilutamide plus ADT appears to be a less cost-effective strategy compared to bicalutamide plus ADT for the first-line treatment of high-volume mHSPC in China.